Perilaku Komunikasi dalam Adaptasi Budaya Ngopi Pada Masyarakat Kota Kediri di Era Pandemi Convid-19 - Prilani; Citra Orwela (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2022)
Recently, there is the change occurring in coffee consuming behavior during the Covid-19 pandemic. Before the pandemic, people in Kediri city have a habit, namely ‘Cangkrukan’, which are people gather together at coffee shop. This research will discuss the changes of behavior to the people in coffee culture during pandemic for two years. The research will result coffee consuming behavior in the Kediri society. The objective of research was to find out the change of coffee consuming behavior and consuming society culture in Kediri coffee shops in facing pandemic. The theory employed in this study was Fredrick Herzberg motivation’s theory and Elton Mayo behavioral management theory. This study employed a phenomenological approach, aiming to explore the change of behavior on the coffee culture during pandemic in Kediri city. The data collection was conducted using direct observation and in-depth interview. The result of research showed that people behavior in Kediri society had changed throughout the pandemic.